Assessing the Effects of Regimented Administrative Structure of Education on Pupils Academic Performance of Basic Schools in Military Barracks, Ghana - Edward Brenya; Dominic Degraft Arthur; Raymond Opoku; Sylvester Atta Andam (Journal of Social and Development Sciences, 2021)
Over the last five years, there has been a downward trend in the BECE performance by pupils in the Basic schools of military barracks in Ghana. The military high command has been concerned about the current performance of pupils in the BECE, and the responsibility lies with the Directorate of Education of the Ghana Armed forces to undertake all efforts at reversing the tide. The study is predicated upon the need to explore all possible causes of a consistent downward trend of BECE performance over the past five years. It is speculated that in the case of the Armed Forces schools, the quality of education could either be significantly enhanced or diminished by the peculiarity of the administration. Thus, the study quantitatively examined the place of military culture as a part of the administration and how the phenomenon impacts academic performance. The findings revealed that not only does military culture impact teacher work output, but the coercive nature of the relationship between the Educational Officers and civilian teaching staff is detrimental to the academic environment. Therefore, this paper recommends that the coercive administrative approach be modified to allow for a much more cooperative and social approach, which would create a conducive and free environment for academic work and consequently improve academic performances.